Relation Between Social Support Received and Provided by Parents of Children, Adolescents and Young Adults With Cancer and Stress Levels and Life and Family Satisfaction - Melguizo-Garín, Anabel; Martos-Méndez, Mª José; Hombrados-Mendieta, Isabel; Ruiz-Rodríguez, Iván (Frontiers in Psychology, 2022)
Introduction: The present study aims at analysing how social support received and provided by parents of children diagnosed with cancer affects their stress levels and life and family satisfaction. Materials and Methods: 112 parents of children who had been diagnosed with cancer and who received treatment in Malaga participated in the study. Data were gathered through self-assessment tools. Results: There is a significant negative relation between social support received and provided and stress levels, as well as a significant positive relation between these two types of social support and life and family satisfaction. Social support received reduces stress and increases family satisfaction, while social support provided increases life satisfaction in parents of children with cancer. Discussion: Analysing social support received and provided allowed us to broaden the knowledge on the effect social support has on stress levels, life satisfaction and family satisfaction in parents of children diagnosed with cancer. This may have relevant practical implications for the design of interventions that would improve parents’ quality of life.